THE PATH TO SELF-RADICALIZATION: READINGS INTO THE CASE OF MARTIN ‘AHMAD’ COUTURE-ROULEAU (AHMAD LE CONVERTI) - Bensaid, Benaouda (Journal of Al-Tamaddun, 2017)
In the morning of October 20th 2014, Martin ’Ahmad’ Rouleau or Ahmad Le Converti, a Canadian Muslim convert from Quebec, Canada, slammed a car into two Canadian Armed Forces members in the parking lot of a Service Canada in Saint-Jean-Sur-Richelieu. The attack caused the tragic death of Warrant Officer Patrice Vincent, a long-serving member of the Armed Forces. Rouleau was later pursued and killed. This incident not only manifests without doubt the disturbing and active manipulation of religious ideology, but also poses the beginning of complex and interrelated problems that cannot be singlehandedly dismissed; significant given the unique danger it poses to both national and international security. Rouleau’s case presents us with an intense interplay between religious conversion, Canadian citizenship, religious interpretation, online religious learning, self-radicalization and the resultant shaping of a destructive malign ’lone-wolf’ terrorist and the ensuing security threat it imposes. This paper would trace the journey of self-guided radicalization undergone by Rouleau, tracking the emotional, personal, psychological and religious influences that culminated in the unexpected violence that shook a nation that so strongly identifies with the preservation of human dignity and life.